2021
DOI: 10.3389/fnagi.2021.765252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex, Age, and Apolipoprotein E Genotype on Brain Ceramides and Sphingosine-1-Phosphate in Alzheimer’s Disease and Control Mice

Abstract: Apolipoprotein ε4 (APOE)4 is a strong risk factor for the development of Alzheimer’s disease (AD) and aberrant sphingolipid levels have been implicated in AD. We tested the hypothesis that the APOE4 genotype affects brain sphingolipid levels in AD. Seven ceramides and sphingosine-1-phosphate (S1P) were quantified by LC-MSMS in hippocampus, cortex, cerebellum, and plasma of <3 months and >5 months old human APOE3 and APOE4-targeted replacement mice with or without the familial AD (FAD) background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 91 publications
(117 reference statements)
2
9
0
Order By: Relevance
“…Furthermore, alterations in sphingosine‐1‐P levels were described in brain tissue and serum of individuals suffering from age‐related neurodegenerative and cardiovascular diseases (Velazquez et al, 2021 ). Our results (validated in independent cohorts) indicated that the levels of this sphingolipid decreased with age in both women and men, although some papers indicated sex‐specific regulation in both plasma (Guo et al, 2014 ) and brain tissue (den Hoedt et al, 2021 ) in human beings and animal models. The negative correlation of sphingosine‐1‐P levels with aging could explain, at least partially, the physiological cognitive decline characteristic of the aging process.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, alterations in sphingosine‐1‐P levels were described in brain tissue and serum of individuals suffering from age‐related neurodegenerative and cardiovascular diseases (Velazquez et al, 2021 ). Our results (validated in independent cohorts) indicated that the levels of this sphingolipid decreased with age in both women and men, although some papers indicated sex‐specific regulation in both plasma (Guo et al, 2014 ) and brain tissue (den Hoedt et al, 2021 ) in human beings and animal models. The negative correlation of sphingosine‐1‐P levels with aging could explain, at least partially, the physiological cognitive decline characteristic of the aging process.…”
Section: Discussionsupporting
confidence: 60%
“…In mice, APP SL females (characterized by the presence of Aβ plaques in the frontal cortex) presented decreased levels of ceramides containing saturated fatty acids and increased levels of ceramides containing unsaturated fatty acids compared to APP SL males (Barrier et al, 2010). Opposite results were found in the AD mouse model based on the APOE4 expression (den Hoedt et al, 2021). Likewise, sex influenced the hippocampal sphingolipid profile in healthy humans carrying the APOE4 genotype (>65 years old): total ceramides, SM, and sulfatides were increased in males but not in females (Couttas et al, 2018).…”
Section: Brain Lipid Changes: Effect Of Sex On Neurodegenerative Dise...mentioning
confidence: 91%
“…Studies using different experimental models demonstrated that the sphingolipid profile in the cortex showed a sex‐specific pattern (Barrier et al, 2010; den Hoedt et al, 2021). In mice, APP SL females (characterized by the presence of Aβ plaques in the frontal cortex) presented decreased levels of ceramides containing saturated fatty acids and increased levels of ceramides containing unsaturated fatty acids compared to APP SL males (Barrier et al, 2010).…”
Section: Brain Lipid Changes: Effect Of Sex On Neurodegenerative Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipid analysis was performed according to Mielke et al [ 44 ] and described previously [ 45 ]. Of the lipid extracts from CSF, plasma and DGUC fraction, 5, 5 and 10μl were injected by an autosampler (Shimadzu, Kyoto, Japan) into a Shimadzu HPLC system (Shimadzu) equipped with a Kinetex C8 column (50×2.1 mm, 2.6μm, Phenomenex, Maarssen, the Netherlands) at 30°C.…”
Section: Methodsmentioning
confidence: 99%